Development of an agroecological strategy with rural women based on a food consumption score - Álvarez-Sánchez, David; Bacca-Acosta, Pedro Pablo; Luna-Mancilla, Lizeth Tatiana; Argoti-Eraso, Roberto; Riascos-Delgado, Marcela; Borja-Tintinago, Jhon James; Rodríguez-Valenzuela, Jeisson (Revista de Ciencias Agrícolas, 2025)
In rural Colombia, female-headed households represent a vulnerable group regarding food insecurity, highlighting the need for strategies to improve the diversity and volume of cultivated food. This study aimed to develop an agroecological strategy using the Food Consumption Score (FCS) as an indicator. To achieve this, we worked with 38 participants from the Obonuco district in the department of Nariño, conducting an initial characterization through a semi-structured survey and applying the FCS methodology to identify at-risk food groups that could be managed. This information served as the foundation for the participatory design of two gardens based on agroecological principles, and over a year, the contribution of these gardens to the prioritized food groups was evaluated. The results revealed that age, education level, and land access increase vulnerability in this population. Based on the FCS results, the gardens were designed to positively impact five food groups by integrating 15 plant species and two animal protein sources (guinea pigs and eggs). The project enhanced food security among rural women heads of households through participatory strategies, the FCS indicator, and agroecological production processes, creating a methodological framework that can be replicated in similar initiatives.